Insights into the mechanism of copper transport by the Wilson and Menkes disease copper-transporting ATPases - Fatemi, Negah; Sarkar, Bibudhendra (Inorganica Chimica Acta, 2002)
Menkes and Wilson diseases are two closely related hereditary disorders of copper metabolism. The genes for these disorders have been cloned and identified as copper-transporting ATPases, which are members of a large family of cation transporters, the P-type ATPases. In addition to the conserved domains common to the P-type ATPase family, the Menkes and Wilson copper transporting ATPases have large cytoplasmic N-termini comprised of six copper-binding domains, each of which contains the copper-binding motif GMT/HCXXC. The structural and functional aspects of copper transport by these transporters have been the subject of intense research in our laboratory as well as those of others. The findings from these studies have been reviewed and used together with homology modeling of the Wilson disease copper transporting ATPase based on the X-ray structure of the sarcoplasmic reticulum Ca-ATPase, to present a hypothetical model of the mechanism of copper transport by copper transporting ATPases. The Wilson and Menkes disease copper-transporting ATPases are members of a large family of cation transporters, the P-type ATPases. Structural and functional studies have been reviewed and used together with homology modeling, to present a hypothetical model of the mechanism of copper transport by copper-transporting ATPases.